PENAFSIRAN QURAISH SHIHAB TENTANG AL-FATH DALAM QS. AL-NASHR - Budiman, Ade (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
Every interpretation is a product of a mufassir, so that different interpreters, it will be have different products. This is going to try to be revealed in this article. However, this interpretation will be discussed is the interpretation of one of the characters Indonesian interpreter, M. Quraish Shihab. We explain it by review this monumental work, Tafsir al-Misbah. Differences in interpretation that will be shown taking sample of the word al-Fath in the surah al-Nasr. This paper concludes that the meaning of al-Fath in the Tafsir al-Mishbah is opening everything covered, either in the form of material and spiritual. Thus, al-Fath covers two things; the first, something that can be reached with a biological eye (and other senses), such as; open the door and close it. Secondly, something which can be reached with the eyes psychological, such as; opening distress and eliminate misery.